An assessment of factors that contribute to the sesual abuse of disabled women in rural areas; the case of Bikita district ward 3 - Mandebvu, Yeukai P. J. (Midlands State University, 2017)
The Research Thesis has the aim of assessing the factors that contribute to the sexual abuse of disabled women in rural areas using the case study of Bikita District Ward 3. The study will focus on the plight of disabled women in Bikita District Ward 3, the factors that subject them to sexual abuse as well as the possible response mechanisms that can be implemented in a bid to reduce the rates of the sexual abuse of disabled women in rural areas. The Researcher was motivated to carry out a research of this nature by the alarming rates of sexual abuse regarding disabled women in rural areas. If sustainable development is to be realised then there is need for attention to shift to the adherence of Human Rights. Qualitative research methodology was used to carry out the research. The Researcher found out that disabled women are the poorest of the poor especially in rural areas. This perhaps is because of their incapability to earn a sustainable living because of socio-economic and cultural dynamics. They depend on caregivers for sustenance. They live in an environment which is characterised by stigmatisation and discrimination which act as social barriers. Indeed their disabilities make them vulnerable to sexual abuse because of the dynamics that are propounded by different disabilities but other factors such as cultural assumptions, social construction, economic considerations as well as poor development initiatives act as catalysts that foster the sexual abuse of disabled women. Therefore it is imperative for the government as well as the 3rd sector to collaborate so as to reduce the vulnerability of disabled women in rural areas. Taking such a stance will reduce the sexual abuse of disabled women.